(untitled) (Research, Society and Development, 2020)
Tomato is a fruit rich in bioactive compounds like lycopene, vitamin C and phenolic compounds. However, cultivation conditions can influence the concentration of these substances. In this study, the objective was to analyze quality characteristics of tomato fruits in different cultivation systems. The following characteristics were evaluated: pH, soluble solids content, total acidity, relationship between soluble solids content and total acidity, instrumental color parameters (L *, a *, b *, chroma and hue), texture, bioactive compounds (total carotenoids, lycopene, total phenolic compounds and vitamin C) and antioxidant activity of grape tomato fruits grown in a greenhouse in different systems (soil x substrate). A completely randomized design was used, with two treatments and four replications. The analysis were performed by official methods and in triplicate. The pH, soluble solids, texture, color, lycopene, vitamins C and antioxidant activity were not affected by the cultivation system used. However, grape-type tomatoes grown in substrate showed higher levels of carotenoids (36.31 µg.100 g-1 fresh matter), phenolic compounds (68.37 mg GAE.100 g-1 fresh matter) and ratio between total soluble solids and total acidity (17.90), and lower total acidity (0.58% citric acid 100 g-1), which represents a nutritional, sensorial and functional advantage for the consumer.